The TNB electricity technology research for reliable and efficient delivering system in Malaysia (Near Term) - 367552 Norhafizah Mustafa Kamal (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2006